Wireless Internet Security Architecture and Protocols - Kempf, James (Cambridge University Press, 2013)
The book begins with an introduction to the topics of security threats in wireless networks, security services for countering those threats, and the process of defining functional architecture for network systems. Examples of cryptographic algorithms are included, and the author goes on to discuss examples of wireless Internet security systems such as wireless network access control, local IP subnet configuration and address resolution, IP mobility, and location privacy. Each chapter describes the basic network architecture and protocols for the system under consideration, the security threats faced, a functional architecture for the security system mitigating the threats, and the important Internet protocols that implement the architecture. The text is an ideal resource for graduate students of electrical engineering and computer science, as well as for engineers and system architects in the wireless network industry.